Diagnostic Accuracy of Urinary Cytokeratin 19 Fragment for Endometriosis. (May 2015) - Lessey, B. A.; Savaris, R. F.; Ali, S.; Brophy, S.; Tomazic-Allen, S.; Chwalisz, K.
Endometriosis affects up to 10% of women of reproductive age and 176 million women worldwide. The prevalence in women with infertility is between 30% and 50% but may be higher in women with pelvic pain, interstitial cystitis, or irritable bowel syndrome. Cytokeratin 19 has been suggested as a potential biomarker in urine for the diagnosis of this condition. The objective of this study was to prospectively determine the accuracy and the performance of a urinary cytokeratin 19 (uCYFRA 21-1) test for diagnosing endometriosis. Ninety-eight consecutive women who underwent laparoscopy had a urinary sample obtained before surgery and were included in the study. Endometriosis was diagnosed by laparoscopy and pathology in 64.3% (63 of 98 women). The estimates and 95% confidence intervals for sensitivity, specificity, positive and negative predictive values, and likelihood ratios were 11.1% (4.5%-21.5%), 94.3% (80.8%-99.3%), 77.7% (39.9-97.1), 37% (27-47.9), 1.94 (0.43-8.86), and 0.94 (0.84-1.06), respectively. Despite the high specificity, the uCYFRA 21-1 test has limited value for clinical practice to discriminate between women with and without endometriosis.